The Impact of the Physical Environment on Intrapartum Maternity Care: Identification of Eight Crucial Building Spaces. (October 2019) - Setola, Nicoletta; Naldi, Eletta; Cocina, Grazia Giulia; Eide, Liv Bodil; Iannuzzi, Laura; Daly, Deirdre
Objectives, Purpose, or Aim: This article investigates whether the physical environment in which childbirth occurs impacts the intrapartum intervention rates and how this might happen. The study explores the spatial physical characteristics that can support the design of spaces to promote the health and well-being of women, their supporters, and maternity care professionals. Background: Medical interventions during childbirth have consequences for the health of women and babies in the immediate and long term. The increase in interventions is multifactorial and may be influenced by the model of care adopted, the relationships between caregivers and the organizational culture, which is made up of many factors, including the built environment. In the field of birth architecture research, there is a gap in the description of the physical characteristics of birth environments that impact users' health. Method: A scoping review on the topic was performed to understand the direct and indirect impacts of the physical environment on birth intervention rates. Results and Discussion: The findings are organized into three tables reporting the influence that the physical characteristics of a space might have on people's behaviors, experiences, practices and birth health outcomes. Eight building spaces that require further investigation and research were highlighted: unit layout configuration, midwives' hub/desk, social room, birth philosophy vectors, configuration of the birth room, size and shape of the birth room, filter, and sensory elements. Conclusions: The findings show the importance of considering the physical environment in maternity care and that further interdisciplinary studies focused on architectural design are needed to enrich the knowledge and evidence on this topic and to develop accurate recommendations for designers.